(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Microbiomes, the diverse communities of microorganisms inhabiting different parts of the human body, are increasingly recognized for their roles in maintaining health. This review summarizes the structure and function of the human microbiome, focusing on the gut, skin, and oral microbiomes. It discusses how microbiomes influence immune function, metabolism, and disease development, with emphasis on the gut microbiome’s role in nutrition and immunity. By highlighting advances, current limitations, and future directions in microbiome research, this article underscores the potential for microbiome-targeted therapies to address various health issues.